Applying Cooperative Learning Using the Jigsaw Type to Improve the Reading Ability of Second-Semester D Class Students at STAIN Jember in the 2011/2012 Academic Year - Suparwoto Sapto Wahono (Fenomena, 2012)
This research was conducted to improve students' reading skills using the jigsaw technique. Reading skills, especially in English, are crucial to master as they enhance knowledge acquisition. Additionally, this technique supports students in comprehending English literature. The conclusion of this study is that the jigsaw technique can improve students' reading skills by dividing them into groups of five members, where each member becomes an expert in their group to convey the content of the text. Penelitian ini dilakukan untuk meningkatkan kemampuan mahasiswa dalam keterampilan membaca dengan menggunakan teknik jigsaw. Keterampilan membaca, khususnya dalam bahasa Inggris, sangat penting untuk dikuasai karena dapat meningkatkan pengetahuan mereka. Selain itu, teknik ini mendukung mereka dalam memahami literatur berbahasa Inggris. Kesimpulan dari hasil penelitian ini adalah teknik jigsaw dapat meningkatkan kemampuan mahasiswa dalam keterampilan membaca dengan cara membagi mahasiswa ke dalam beberapa kelompok yang terdiri dari 5 anggota, di mana setiap anggotanya menjadi tim ahli bagi kelompoknya untuk menyampaikan isi teks.